Evaluation of magnetic field assisted sun drying of food samples on drying time and mycotoxin production - Nuroglu, Emine; Oz, Ersoy; Bakirdere, Sezgin; Bursalioglu, Ertugrul Osman; Kavanoz, Huseyin Birtan; Icelli, Orhan (ELSEVIER SCI LTD, 2019)
Mycotoxins are a variety of metabolic products produced by fungi, which can cause various damages to other organisms. The aim of this study was to figure out the effect of new drying methods namely drying in oven under magnetic field and drying under the sun and magnetic field on the mycotoxin formation for some food samples. In this system, a fixed magnetic field of 300 mu T was used for the drying process. The amounts of moisture in the samples dried with the new developed methods were measured in hazelnut (Corylus L.), fig (Ficus calico L.), chili pepper (Capsicum annuum L.) and grape (Vitis vinifera L.) depending on time. Mycotoxin species within different foodstuffs were determined at trace levels by using LC-MS/MS device under the optimum conditions, and the results obtained from the samples dried with the new methods were compared with each other and results of food samples dried by traditional method. The results indicated that the new developed drying methods cause decrease in the drying periods, and the dried samples did not contain any mycotoxin. This study suggested new drying strategies to eliminate the mycotoxin formation. For the analysis of the results, different statistical tests were used. In order to determine which technique works faster in drying the samples, box plots were obtained using descriptive statistics. Mann Whitney tests were also applied to determine if there was a statistical difference between the drying methods.
Keywords: Dried food; Dry process; Magnetic field; Mycotoxin; LC-MS/MS; WATER; CONTAMINATION; SEEDS; Food Science & Technology